2016
DOI: 10.4103/0019-5049.179463
|View full text |Cite
|
Sign up to set email alerts
|

A survey of a population of anaesthesiologists from South India regarding practices for rapid sequence intubation in patients with head injury

Abstract: Background and Aims:Evidence and utility of the individual steps of the rapid sequence induction and tracheal intubation protocols have been debated, especially in the setting of traumatic brain injury. The purpose of this survey was to determine preferences in the current approach to rapid sequence intubation (RSI) in head injury patients among a population of anaesthesiologists from South India.Methods:A questionnaire was E-mailed to all the members of the Indian Society of Anaesthesiologists’ South Zone Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…High variability in the modalities of rapid sequence intubation has been reported in national surveys and randomized clinical trials published between 2015 and 2020 . Rapid sequence intubation without neuromuscular blockers was performed in 25% to 75% of patients at risk of aspiration .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High variability in the modalities of rapid sequence intubation has been reported in national surveys and randomized clinical trials published between 2015 and 2020 . Rapid sequence intubation without neuromuscular blockers was performed in 25% to 75% of patients at risk of aspiration .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 High variability in the modalities of rapid sequence intubation has been reported in national surveys and randomized clinical trials published between 2015 and 2020. [4][5][6][7][8] Rapid sequence intubation without neuromuscular blockers was performed in 25% to 75% of patients at risk of aspiration. [4][5][6][7][8] This observation is possibly explained by concerns about potential severe adverse effects of neuromuscular blockers, including anaphylaxis, 9 prolonged curarisation, 10 metabolic disturbance, 11 and postoperative respiratory complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from India for RSI in patients with head injury revealed the predominant use of rocuronium over suxamethonium. [9] However, the ratio was less impressive as compared to the other study from Germany. [17] In the Indian study, most of the anaesthetists used rocuronium (44%), followed by suxamethonium (39%).…”
Section: Discussionmentioning
confidence: 69%
“…The current literature suggest that the existing diversity regarding choice of drugs for RSI might be at least country specific. [8,9] Therefore, the aim of the present study is to describe the current practice of emergency physicians and anaesthesiologists with respect to the selection of drugs for RSI in trauma patients in a single institute with a level I trauma centre.…”
Section: Introductionmentioning
confidence: 99%